2019
DOI: 10.4103/picr.picr_29_18
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of Pharmacovigilance Programme of India in containment of antimicrobial resistance in India

Abstract: Misuse of antimicrobials has become one of the grave concerns of public health. In last two decades, this has been largely contributing in the emergence of antimicrobial resistance (AMR) among all the pathogens. A 2013 report of Centres for Disease Control and Prevention, USA figured that at least 2 million people get an antibiotic-resistant infection every year and as many as 23,000 people lost their life. A multi-country survey in Southeast Asia region conducted by World Health Organization (WHO) in 2015, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Indian healthcare institutions get accreditation from bodies such as the National Accreditation Board for Hospitals and Healthcare providers (NABH). The IPC has signed a Memorandum of Understanding (MoU) with the NABH, under the Quality Council of India (QCI), to ensure for total cooperation of the hospitals on the reporting of adverse events associated with medical devices in the hospital [10].…”
Section: Accreditation Bodiesmentioning
confidence: 99%
“…Indian healthcare institutions get accreditation from bodies such as the National Accreditation Board for Hospitals and Healthcare providers (NABH). The IPC has signed a Memorandum of Understanding (MoU) with the NABH, under the Quality Council of India (QCI), to ensure for total cooperation of the hospitals on the reporting of adverse events associated with medical devices in the hospital [10].…”
Section: Accreditation Bodiesmentioning
confidence: 99%
“…However, close and continuous surveillance for quick detection of inappropriate use and the appearance of AMR can be difficult, especially because well-equipped laboratories with trained personnel can be scarce in certain settings [9,25]. Hence, another helpful and inexpensive strategy has been suggested for challenging scenarios: the use of pharmacovigilance (PV) data to report suspected cases of AMR, therapeutic failure, and inappropriate or off-label use of AB [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific community continues to propose innovative antimicrobials monitoring approaches, and some have suggested pharmacovigilance data as a potential source of information for antimicrobial stewardship programs [ 18 ]. Recent studies have underlined the potential role of Pharmacovigilance in containing rising antimicrobial resistance [ 19 , 20 ], proposing methods and tools that pharmacovigilance can offer to programs that monitor suspected resistance or cases of inappropriate use of antimicrobials. A study conducted in Russia concluded that the most frequent types of medication errors (“administration of an antibiotic in the absence of indications/wrong indication”, “incorrect dosage and regimen”, and “administration of a contraindicated drug”) associated with the use of beta-lactams were the leading risk factors of growing bacterial resistance [ 21 ].…”
Section: Introductionmentioning
confidence: 99%